AN AUDIT OF INFORMED CONSENT IN SURGICAL PATIENTS AT A UNIVERSITY HOSPITAL - Siddiqui, Faisal Ghani; Shaikh, Jan Mohammad; Memon, Mohammad Munir (Journal of Ayub Medical College Abbottabad, 2010)
Background: To obtain informed consent is considered an integral part of modern clinical practice. It works as a safeguard of patient's rights and minimizes the chances of legal action against the physician in case of any complication arising from the proposed therapy. Objective was to evaluate the practice of informed consent in patients undergoing surgery in a University hospital. Methods: A survey was conducted at different surgical departments of a university hospital during December 2007 to March 2008. Participants were selected from patients over the age of 18 years who had undergone elective or emergency surgery. All interviews were based on structured questionnaire. The patients were asked if an informed consent was taken or not before the surgery. They were also inquired if they were given information about the diagnosis, the surgical procedure planned and risks associated with it. The patients were also asked if they were informed about the types of anaesthesia proposed. Results: A total of 106 patients were randomly selected for this study. In 8.5% cases, no consent was taken. Only 38% of the surveyed patients acknowledged that they actually understood the information imparted to them. 66% patients were informed about the type of anaesthesia proposed but none was given any hint about complications of anaesthesia. 11% patients actually signed the consent forms themselves. Conclusion: The quality of existing informed consent process in a university hospital is less than ideal. There is a great need to educate the doctors and healthcare regarding the importance of patient's autonomy and their right to the information about their medical condition and the proposed surgical procedures to ensure their participation in the decision making regarding their treatment. Keywords: Informed consent, audit, postoperative patients